The effect of strategy, information asymmetry, and incentive scheme on budgetary slack in family business company - Janet Anneta; Jesica Handoko (Journal of Accounting and Investment, 2024)
Research aims: This research focuses on testing the influence of implementing strategies by the company, the influence of information asymmetry that occurs between parties in the organization, and the incentive system applied in the organization to its employees.Design/Methodology/Approach: Computerized experimental research was conducted using a 2x2x2 mixed-subject research design, where there were two between-subject variables and one within-subject variable. Participants in this research were employees of family business companies involved in preparing the company budget. This test used the ANOVA analysis tool with Repeated Measurement.Research findings: This research provides results that the information asymmetry variable had a positive effect on the emergence of budgetary slack, while the variables of strategy, incentive scheme, and the interaction of each variable have not proven to influence the emergence of budgetary slack.Theoretical contribution/Originality: The experimental findings support the agency problem that arises from information asymmetry.Practitioner/Policy implication: By using practitioners conditioned in specific budgeting situations in experimental budget studies, this research provides practical implications for budgeting problems in business practice. In particular, it provides an overview of the factors that can influence budget gaps, and in this case, a business can condition its efforts in taking advantage of conditions to create the right budget. Apart from that, this research will be able to provide an overview of what treatments can encourage motivation and increase opportunities for the tendency to create budget slack.Research limitation/Implication: This study was limited to certain company sectors, and there is the possibility of a gap in understanding and interpreting the experimental scenario.